Networks in agri-food systems: Configuration, transformation and lessons from the “AgriLAC Resiliente” Initiative - Quintero, Katherine; Reyes, Byron; Lopera, Diana Carolina (2025)
This study analyzes how the AgriLAC Resiliente Initiative has transformed collaboration networks in Latin American agri-food systems. Using Social Network Analysis and a “usable past” baseline reconstruction, we compare actor-to-actor collaboration before and after the intervention. Results show increased connectivity, more cohesive structures, and the integration of new organizations. Despite these gains, the network remains sparse and some actors stay peripheral. The findings highlight both progress and remaining challenges for strengthening coordination, learning, and innovation across agri-food systems.